Can monetary policy affect the real economy? - Philip Arestis; Malcolm Sawyer (Levy Economics Institute of Bard College, 2002)
Current monetary policy involves the manipulation of the Central Bank interest rate (the repo rate), with the specific objective of achieving the goal(s) of monetary policy. The latter is normally the inflation rate, although in a number of instances this may include the level of economic activity (the U.S. Federal Reserve monetary policy is a good example of this category). This raises two issues. The first is the theoretical underpinnings of this mode of monetary policy. The second is the channels of monetary policy or, more concretely, the channels through which changes in the rate of interest may affect the ultimate goal(s) of policy. Both aspects are investigated in this paper. Furthermore, we suggest that it is imperative to consider the empirical estimates of the effects of monetary policy. We summarise results drawn from the eurozone, the U.S. and the UK and suggest that these empirical results point to a relatively weak effect of interest rate changes on inflation. We also suggest, on the basis of the evidence adduced in the paper, that monetary policy can have long-run effects on real magnitudes. This particular result does not fit comfortably with the theoretical basis of current thinking on monetary policy.
Keywords: 330